2003
DOI: 10.1007/s00442-002-1157-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and carbon isotopic composition of leaf wax in vegetation and aerosols in a northern prairie ecosystem

Abstract: We measured the molecular and carbon isotopic composition of major leaf wax compound classes in northern mixed mesic prairie species (Agropyron smithii, Stipa viridula, Bouteloua gracilis, Tragopogon dubius) and in selected crops (Triticum aestivum, Brassica napus, Hordeum vulgare, Medicago sativa) of southern Alberta and also in aerosols collected 4 m above the prairie canopy. Our aims were to better constrain the wax biosynthetic carbon isotopic fractionation relative to the plant's carbon isotopic discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 43 publications
8
44
0
Order By: Relevance
“…Lastly, the CPI values, molecular distribution, as well as the δ 13 C values for the n-alkanes and n-alkan-1-ols are similar to those found at present in air masses originating from the North American continent (Conte and Weber, 2002;Conte et al, 2003) and significantly different from those found in dust originating from Northern Africa (Conte and Weber, 2002;Huang et al, 2000;Schefuss et al, 2003a), at present the largest source of dust in the world. In this regard, the most distinct features are the dominance of the C 26 -homologues in the n-alkan-1-ol and n-alkanoic acid molecular distributions (Fig.…”
Section: Source Higher Plant Waxessupporting
confidence: 55%
See 2 more Smart Citations
“…Lastly, the CPI values, molecular distribution, as well as the δ 13 C values for the n-alkanes and n-alkan-1-ols are similar to those found at present in air masses originating from the North American continent (Conte and Weber, 2002;Conte et al, 2003) and significantly different from those found in dust originating from Northern Africa (Conte and Weber, 2002;Huang et al, 2000;Schefuss et al, 2003a), at present the largest source of dust in the world. In this regard, the most distinct features are the dominance of the C 26 -homologues in the n-alkan-1-ol and n-alkanoic acid molecular distributions (Fig.…”
Section: Source Higher Plant Waxessupporting
confidence: 55%
“…Long-chain n-alkanes (C 21 − C 33 ) with a clear odd over even predominance and n-alkan-1-ols (C 22 − C 32 ) with a clear even over odd predominance are common constituents of the epicuticular waxes of terrestrial higher plants such as angiosperms and gymnosperms (e.g., Bianchi, 1995;Eglinton and Hamilton, 1967; see review in Diefendorf et al, 2011). They are a major component of modern dust even in remote ocean areas (Conte and Weber, 2002;Conte et al, 2003;Gagosian et al, 1981;Simoneit et al, 1977) as they can easily be removed from the leaf surface by wind or rain, especially by sandblasting during dust storms, or entrained as part of soil and transported over large distances. Numerous studies therefore used the accumulation of these lipids in distal marine sediments far from major fluvial inputs to infer changes in aeolian input to the open ocean (e.g., López-Martínez et al, 2006;Madureira et al, 1997;Martínez-Garcia et al, 2009.…”
Section: Accumulation Rates Of N-alkanes and N-alkan-1-olsmentioning
confidence: 99%
See 1 more Smart Citation
“…D leaf was lower in AM trees versus AP trees, suggesting lower long-term WUE ( Figure 7B). However, wax composition itself can affect carbon discrimination measurements, as wax is depleted in 13 C relative to total plant carbon (Conte et al, 2003). As such, the higher D leaf in AP could also be a consequence of the higher wax load per surface area.…”
Section: Physiological Traits As a Function Of Alkene Phenotypementioning
confidence: 99%
“…Isotopic fractionation also occurs during subsequent biosynthesis, with depletion generally increasing with the number of steps required for biosynthesis. Thus, lignin of wood is typically depleted by 3.0-4.4‰ relative to cellulose (Benner et al 1987;Goñi and Eglinton 1996;Spiker and Hatcher 1987;Loader et al 2003), and plant lipids are even more depleted in 13 C (Conte et al 2003).…”
mentioning
confidence: 99%